PENGARUH MEDIA SOSIAL TERHADAP PERSEPSI MARRIAGE IS SCARY DI KALANGAN GEN Z - Najwa Fathiyati Shafa; Hasna Nur Latifah; Putri Puspita; Popy Susilawati; Rama Wijaya Abdul Rozak (Cahaya Ilmu Bangsa Institute, 2025)
The purpose of this study is to analyze and explain social media use among adolescents, the development of interpersonal relationships, and the influence of social media on the perception of fear of marriage. With the proliferation of social media platforms, norms and values about marriage are increasingly influenced by the content presented, including individual experiences and views shared online. Through questionnaires and content analysis, this study identifies how social media shapes fear and anxiety about marriage among Gen Z. The findings suggest that negative representations of marriage, as well as unrealistic expectations, can reinforce the perception that marriage is something that is scary. This article is expected to provide a deeper understanding of the impact of social media on the younger generation's views of the institution of marriage.